MESIN PENGERING KERUPUK HEMAT ENERGI UNTUK MENINGKATKAN PRODUKTIVITAS PRODUSEN KERUPUK - Sudiyatno, Sudiyatno; Rachmad, Suprapto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2004)
The   objective    of  producing    a  low  energy   drying   machine   is  to  help   chips industries   in  increasing   their  productivity   by  shortening   the  drying  time.  Up  to  now they  use heat of sunlight  to dry the chips.This  process   is time  consuming   and  why  the dry  season  comes,  the  process   isdelayed.   It decreases   the  quality  of chips.The   drying  machine   produced   uses  firewood placed   in a furnace   as the  heat  source.  The  heat  is then  flown  through   pipes  into  the drying  room,  where  wet  chips  are placed.                                               iiThe  room  has a length  of  1.2 m, a height   of  1 m and a width  of 1 m. It has twodoors  and  equipped   with  a thermometer.    Below   the  room,  there  is a furnace   having capacity   of 6 kg tire  wood  and  an oxygen  inlet.  The drying  temperature   is 60 -  70° C. I kg firewood   can  produce  the  heat with  temperature   of 60 - 70° C for  1.5 hours.The drying  process   of wet- chips  takes  about  5 hours.  For that  of  half  dry  chips,  it takes  2hours.  This  machine  has capacity  of2.400   wet chips  and 6.000  half  dry chips.